PERAN DINAS TENAGA KERJA DAN TRANSMIGRASI (DISNAKERTRANS) KOTA SERANG DALAM MENGURANGI TINGKAT PENGANGGURAN TERBUKA - Setiawan, Edo; Sa'adiyyah, Ade Millatus; Mahmud, Toni Anwar (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
This study aims to determine the role of the Department of Manpower and Transmigration (DISNAKERTRANS) of Serang City in reducing the open unemployment rate. The research method used is qualitative method. The source of data in this qualitative research is by digging up information / information directly from sources of information that are considered related. The result of this research shows that DISNAKERTRANS of Serang City plays a major role in the effort to reduce unemployment through its work program, namely organizing the employment information system; implementing training, apprenticeship and labor productivity; implementing placement and expansion of employment opportunities; implementing the development of industrial relations and work requirements; and implementing the development and supervision of labor norms. However, from the work program, the role of DISNAKERTRANS in efforts to reduce the unemployment rate has not fully run optimally. Many obstacles hinder its realization, especially in terms of facilities, budget and effectiveness of labor absorption so that the unemployment rate is still high.